Computer Mediated Communication, The Way for Developing Students’ Arabic Writing Ability - Albar Adetary Hasibuan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Computer Mediated Communication, better known as CMC, can be used as a tool in improving students' Arabic writing skills. CMC is used because computers and networks are familiar to students now. CMC can also make learning to write Arabic more creative and innovative. The purpose of writing this article is to provide information about computer-mediated communication (CMC) and also how to apply CMC to learning to write Arabic, to improve student writing skills.يمكن استخدام التواصل عبر الكمبيوتر ، المعروف باسم CMC ، كأداة لتحسين مهارات الطلاب في الكتابة باللغة العربية. يتم استخدام CMC لأن أجهزة الكمبيوتر والشبكات مألوفة لدى الطلاب الآن. يمكن أن تجعل CMC تعلم الكتابة العربية أكثر إبداعًا وابتكارًا. الغرض من كتابة هذه المقالة هو توفير معلومات حول التواصل عبر الكمبيوتر (CMC) وأيضًا كيفية تطبيق CMC على تعلم الكتابة باللغة العربية ، لتحسين مهارات كتابة الطلاب.